A system for generating research impact visualizations over medical research groups. Issue 2 (3rd April 2018) - Mischo, William H.; Schlembach, Mary C.
Abstract: Universities routinely employ research impact assessment mechanisms and tools for grant proposals, resource allocation decisions, and funding budget requests. These impact metrics are often displayed in interactive visualizations and dashboard displays. There is a growing trend for libraries to be cooperatively involved in the gathering and provision of research intelligence and impact data. The University of Illinois at Urbana-Champaign Library has developed a system for generating research impact visualizations for research groups within the newly established Carle Illinois College of Medicine. Using the Elsevier Scopus database Applications Programming Interface, we have created a series of scripts to extract article, conference paper, and book chapter metadata and build supporting database tables. From the database, a dashboard visualization of scaled and clickable display bubbles and publication number labels is generated for each individual researcher. The interactive visualization can retrieve articles and papers published over the last five years, citation information (as cited by number) for each researcher, National Science Foundation and National Institutes of Health grant matches, and a visualization of the coauthored papers for each author within the cohort. These activities enhance the role of the library in supporting knowledge management and scholarly communication and in fostering campus partnerships and collaborations.